2020
DOI: 10.3390/molecules25092203
|View full text |Cite
|
Sign up to set email alerts
|

Grape Cane Extracts as Multifunctional Rejuvenating Cosmetic Ingredient: Evaluation of Sirtuin Activity, Tyrosinase Inhibition and Bioavailability Potential

Abstract: Grape canes are waste biomass of viticulture containing bioactive polyphenols valuable in cosmetics. Whereas several studies reported the cosmetic activities of E-resveratrol, only few described the potential of E-ε-viniferin, the second major constituent of grape cane extracts (GCE), and none of them investigated GCE as a natural blend of polyphenols for cosmetic applications. In this study, we considered the potential of GCE from polyphenol-rich grape varieties as multifunctional cosmetic ingredients. HPLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…Currently, few possible applications for this residue are reported; some examples include as a precursor of activated carbon or raw material for the production of biosurfactants [ 9 , 10 ]. Conversely, the exploitation of grape canes as a novel and cheap source of bioactive compounds, such as polyphenols, is poorly investigated, and the potential of grape cane extracts as multifunctional active ingredients in cosmetic formulations for skin care was very recently described [ 11 ]. These molecules, thanks to their well-known strong antioxidant power, are of significant interest for use in the food, cosmetic and pharmaceutical industries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, few possible applications for this residue are reported; some examples include as a precursor of activated carbon or raw material for the production of biosurfactants [ 9 , 10 ]. Conversely, the exploitation of grape canes as a novel and cheap source of bioactive compounds, such as polyphenols, is poorly investigated, and the potential of grape cane extracts as multifunctional active ingredients in cosmetic formulations for skin care was very recently described [ 11 ]. These molecules, thanks to their well-known strong antioxidant power, are of significant interest for use in the food, cosmetic and pharmaceutical industries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both compounds showed higher tyrosinase inhibitory effects than the positive control, kojic acid which is the known skin whitening constituent ( Table 1 and Figure S4 ). In previous studies, ε-viniferin ( 1 ) is reported to have tyrosinase inhibitory activity [ 23 ]; however, vitisin B ( 2 ) was first identified in our study.…”
Section: Resultsmentioning
confidence: 57%
“…First, two constituents expected to have tyrosinase inhibitory activity were isolated from the EtOAc fraction and their bioactivity evaluated. The structures of the isolated compounds 1 and 2 were identified as ε-viniferin ( 1 ) [ 20 , 21 ] and vitisin B (γ-viniferin, 2 ) [ 21 , 22 , 23 ], respectively, using 1 H-NMR, 13 C-NMR, and ESI-MS ( Figure 2 , Figures S2 and S3, and Table S2 ). In tyrosinase inhibitory assay, the IC 50 values of compounds 1 , 2 , and kojic acid were 3.51, 10.74, and 27.09 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids possess significant antiallergic, antihepatotoxic, anti-inflammatory, antioxidant, antitumor, antiviral, antibacterial, antiosteoporosis as well as cardio-protective activity. Antioxidant, antihepatotoxic, anti-inflammatory, antiallergic, antitumor, antiosteoporosis, antiviral, antibacterial and cardio-protective potential have been reported in many flavonoids from various plant species [5][6][7][8][9]. In vivo studies also support the possible use of flavonoid rich plants in treating diseases.…”
Section: Introductionmentioning
confidence: 86%